2021
DOI: 10.1177/17470161211003021
|View full text |Cite
|
Sign up to set email alerts
|

Queer considerations: Exploring the use of social media for research recruitment within LGBTQ communities

Abstract: The use of social media platforms (such as Facebook) for research recruitment has continued to increase, especially during the global COVID-19 pandemic. Social media enables researchers to reach diverse communities that often do not have their voices heard in research. Social media research recruitment, however, can pose risks to both potential participants and the researchers. This topic paper presents ethical considerations related to social media recruitment, and offers an example of harassment and hate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Social media advertising has been used successfully in previous studies of hard-to-reach populations, including sexual minorities (King et al, 2014 ; Thornton et al, 2016 ). Although not without its risks and limitations (Littler & Joy, 2021 ), this method allows recruitment of LGBTQ sub-populations that are underrepresented in research, including older adults, those in non-Western and rural regions, and those not highly involved in the LGBTQ community. The latter is important because people higher in community involvement—who are often the primary source for minority stress research—may differ in meaningful ways from those who are less community-involved (e.g., in real or perceived exposure to minority stress, or motivation for participating in research; Kuyper et al, 2016 ; Meyer & Wilson, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Social media advertising has been used successfully in previous studies of hard-to-reach populations, including sexual minorities (King et al, 2014 ; Thornton et al, 2016 ). Although not without its risks and limitations (Littler & Joy, 2021 ), this method allows recruitment of LGBTQ sub-populations that are underrepresented in research, including older adults, those in non-Western and rural regions, and those not highly involved in the LGBTQ community. The latter is important because people higher in community involvement—who are often the primary source for minority stress research—may differ in meaningful ways from those who are less community-involved (e.g., in real or perceived exposure to minority stress, or motivation for participating in research; Kuyper et al, 2016 ; Meyer & Wilson, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…To assess why people targeted for RI recruitment were not eager to participate, we analysed comments posted in reply to our recruitment post on Reddit, a social network with a forum-style discussion structure (threads) that works with up-voting and down-voting contents in topic-based communities (sub-Reddits). The research community is divided on how one should approach data exploitation in online communities (Proferes et al, 2021) and how one should recruit in potentially marginalised and vulnerable online communities (Littler & Joy, 2021). However, given thati) our target community was very broad and we published our posts inside unspecific groups with large followings,ii) quotes were translated from the original German, making it much harder to track down the original phrasing,iii) quotes in neither English nor (original) German could be reversed-Google-searched,iv) we removed all usernames and other identifying or personal information in this publication,v) users on Reddit frequently choose fictional usernames and usually share no identifying personal information on their profiles,we concluded that participants’ confidentiality is not threatened and that the social media data at hand can be treated as secondary data.…”
Section: Challenges During the Recruitment Phasementioning
confidence: 99%
“…Researchers facing challenges in participant recruitment, especially from "hard-toreach" or "seldom-heard" populations, are increasingly turning to innovative approaches, such as utilising social media for recruitment and online data collection (Sandhu et al 2023). This method has proven effective in reaching diverse and under-represented groups in research (Guillory et al 2018;Sandhu et al 2023), particularly amidst the COVID-19 pandemic (Littler and Joy 2021).…”
Section: Introductionmentioning
confidence: 99%